Four Essential Tremor Cases with Moderately Impaired Gait: How Impaired can Gait be in this Disease?. (4th November 2013) - Louis, Elan D.; Galecki, Monica; Rao, Ashwini K.
Background: A body of literature is emerging regarding gait/balance impairments observed in essential tremor (ET) patients. Although impairment is generally mild, the full extent of the spectrum remains undefined. We present four ET cases with more severe gait/balance impairment. Methods: A battery of subjective and objective gait/balance assessments was performed: the Activities-specific Balance Confidence Scale, the Berg Balance Scale, and the Tinetti Performance Oriented Mobility Assessment (POMA). Tandem missteps during 10 steps were counted. Quantitative gait testing was performed (GAITRite) to quantify gait speed, dynamic balance, gait symmetry, and gait variability. Results: Two patients were middle-aged (38 and 52 years) and two were older (70 and 79 years). All had longstanding classic ET (duration 22–60 years). The mean POMA score was 21.5, which is indicative of moderate fall risk. On average, there were five missteps during tandem gait, which was higher than observed in substantially older ET cases (age 86.0±4.6 years), and four times higher than seen in ET patients of comparable age. On quantitative gait analysis, patients demonstrated significant balance impairment. Discussion: We present a sample of ET patients with a level of gait difficulty that would not be characterized as mild. The existence of such cases raises a number of questions, one of which is how impaired can gait be in ET?